Using both strands: The fundamental nature of antisense transcription. Issue 1 (2nd January 2016) - Murray, Struan C; Mellor, Jane
ABSTRACT: Non-coding transcription across the antisense strands of genes is an abundant, pervasive process in eukaryotes from yeast to humans, however its biological function remains elusive. Here, we provide commentary on a recent study of ours, which demonstrates a genome-wide role for antisense transcription: establishing a unique, dynamic chromatin architecture over genes. Antisense transcription increases the level of nucleosome occupancy and histone acetylation at the promoter and body of genes, without necessarily modulating the level of protein-coding sense transcription. It is also associated with high levels of histone turnover. By allowing genes to sample a wider range of chromatin configurations, antisense transcription could serve to make genes more sensitive to changing signals, priming them for responses to developmental programs or stressful cellular environments. Given the abundance of antisense transcription and the breadth of these chromatin changes, we propose that antisense transcription represents a fundamental, canonical feature of eukaryotic genes.